Perspectivas de aplicabilidades da extensão universitária por meio das práticas biblioteconômico-informacionais - Frutuoso, Antonio Marcos Ribeiro; Silva, Jonathas Luiz Carvalho (Informação em Pauta, 2024)
It deals with the performance of University Extension through bibliotheeconomic-informational practices. Establishes, in the research problem, how the axes of University Extension can act through practices and activities of the librarian-informational field? Its objective is to address the potential applicability of the axes of University Extension through practices and activities in the library-informational field. It determines the exploratory and descriptive purposes in the methodology, having as a strategy the bibliographic method, which characterizes qualitative research. It concludes that the axes of University Extension make it possible to think about a range of library-informational practices and activities, such as management, technologies, mediation, public policies, services and products, among other means.